Foreign Direct Investment, Diaspora Remittances, and Youth Unemployment in Nigeria - Anyachebelu Uzoma Miriam; Uju Regina Ezenekwe; Uchenna Anyanwu (Journal of Social Science and Economics (JOSSE), 2025)
The current state of sectoral performance reveals that Nigeria’s productivity framework is inherently weak in delivering the desired socioeconomic outcomes in terms of employment generation. This study examined the impact of foreign direct investment and diaspora remittances on youth unemployment in Nigeria from 1986 to 2022. This study employed the autoregressive distributed lag (ADL) approach to achieve its objectives. The dependent variable of this study is youth unemployment, while the independent variables are foreign direct investment, remittances, inflation, and real gross domestic product. The data for these variables were sourced from the Central Bank of Nigeria Statistical Bulletin and the National Bureau of Statistics. The key results indicate that all variables are negatively correlated with youth unemployment, although foreign direct investment and inflation exhibit a significant relationship with youth unemployment at the 0.05 significance level. This study recommended, among other things, the need for the Nigerian government to attract foreign direct investment by improving the ease of doing business and promoting economic growth through infrastructure provision, which will also enhance FDI attraction in Nigeria.